2017
DOI: 10.1556/066.2016.0017
|View full text |Cite
|
Sign up to set email alerts
|

In vitro probiotic potential of Enterococcus species isolated from tungrymbai, a fermented soybean product of Meghalaya, India

Abstract: Lactic acid bacteria were isolated from tungrymbai, a traditional fermented soybean product of Meghalaya, India and assessed for their probiotic properties. Survival under simulated gastric conditions was tested and fi ve acid tolerant strains were selected. By using 16S rDNA sequencing, these isolates were confi rmed to be Enterococcus species. The strains exhibited good survivability in high concentrations of bile salts. The strains were susceptible to antibiotics and they were also found to inhibit growth o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 16 publications
2
2
0
Order By: Relevance
“…For bile salts tolerance, all four isolates retained viability, though with a decreasing tendency during 3 hour of incubation, Similar observations have been made in other studies by [20],who observed that the Enterococcus faecium can survive up till 3.5% of bile salt. It has been argued, that the high tolerance to acid and bile salts by Enterococcus faecium is due to the commensalism of this type of bacteria in the gastrointestinal tract of human and animals [21] .…”
Section: Discussionsupporting
confidence: 90%
“…For bile salts tolerance, all four isolates retained viability, though with a decreasing tendency during 3 hour of incubation, Similar observations have been made in other studies by [20],who observed that the Enterococcus faecium can survive up till 3.5% of bile salt. It has been argued, that the high tolerance to acid and bile salts by Enterococcus faecium is due to the commensalism of this type of bacteria in the gastrointestinal tract of human and animals [21] .…”
Section: Discussionsupporting
confidence: 90%
“…Our findings are consistent with the nontolerance in L. delbruekii isolated from dairy products (Hassanzadazar et al, ), but others have demonstrated the probiotic properties of L. delbrueckii , isolated from home‐made yogurt (Balamurugan et al, ; Handa & Sharma, ). Among the nonstarters, the Enterococcus species (NPL289 and NPL294) were acid‐tolerant, an outcome that aligns with other findings (Malakar, Das, & Deka, ) (Hanchi, Mottawea, Sebei, & Hammami, ). None of the LAB species or strains isolated from commercial yogurt brands had all the desirable probiotic attributes.…”
Section: Discussionsupporting
confidence: 87%
“…plantarum ] ( Zheng et al, 2020 )} used in this study (equivalent to Lpb. plantarum ATCC 8014) has been characterized for its probiotic properties ( Tambekar and Bhutada 2010 ; Sreevani and Kumari 2013 ; Pop et al, 2016 ; Malakar et al, 2017 ; Khalil et al, 2018 ; Monteiro et al, 2019 ). Lpb.…”
Section: Introductionmentioning
confidence: 99%